2017
DOI: 10.1080/21655979.2017.1373532
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis reveals that a global response is induced by subinhibitory concentrations of ampicillin

Abstract: In this study, a recipient-donor co-culture system was used to research the effect of subinhibitory concentrations of antibiotics on horizontal transmission in bacteria and the influence of antibiotics on protein expression. We employed two-dimensional gel electrophoresis combined with mass spectrometry to compare the protein expression profiles in systems with or without 0.5 × the minimum inhibitory concentration of ampicillin. RT-PCR was used to assess the transcriptional levels of the differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…To achieve the sustainable development, the future research directions are suggested as follows. (1) The development of analytical methods for the detection of a greater number of antibiotics and their TPs, in order to improve risk assessments and establish quality standards for antibiotics in the environment; (2) further toxicological studies must be performed on potential chronic effects of antibiotic mixtures and their degradation products at environment-related concentration; (3) understand better and deeper the toxicity of antibiotics toward non-target organisms by proteomic responses and gene expression study; (4) human health may be affected by the consumption of agricultural products polluted by antibiotics, more attention should be paid to the indirect effects of antibiotics caused by the drinking water and food chain; (5) further research is needed to evaluate the relationship between antibiotic contamination and the presence of ARGs/ARB in the environment; (6) elucidation of degradation products and their bioactivity needs to be further investigated; (7) develop efficient and low-cost treatment technology for controlling the emission of antibiotic contaminants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the sustainable development, the future research directions are suggested as follows. (1) The development of analytical methods for the detection of a greater number of antibiotics and their TPs, in order to improve risk assessments and establish quality standards for antibiotics in the environment; (2) further toxicological studies must be performed on potential chronic effects of antibiotic mixtures and their degradation products at environment-related concentration; (3) understand better and deeper the toxicity of antibiotics toward non-target organisms by proteomic responses and gene expression study; (4) human health may be affected by the consumption of agricultural products polluted by antibiotics, more attention should be paid to the indirect effects of antibiotics caused by the drinking water and food chain; (5) further research is needed to evaluate the relationship between antibiotic contamination and the presence of ARGs/ARB in the environment; (6) elucidation of degradation products and their bioactivity needs to be further investigated; (7) develop efficient and low-cost treatment technology for controlling the emission of antibiotic contaminants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Antibiotics have been extensively used for the treatment and prevention of diseases in humans, as well as for protecting animal health and promoting animal growth in aquaculture and livestock industries [ 2 , 7 ]. Recently, due to the global growth in human population and rising demand for animal protein [ 2 ], antibiotic consumption has been growing and reached enormous amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Такі АМП як триметоприм та хінолони інгібують дію ферментів, що взаємодіють із ДНК, і блокують процес реплікації. Мутації у клітинах Escherichia colі зумовлюють також ампіцилін та канаміцин, стимулюючи утворення ROS-продуктів [22,[24][25][26].…”
Section: м а т ер і а л и т а м е то д и д о с л і д ж е н н яunclassified
“…This function was demonstrated only in a few cases (Currie et al, 1999;Neeno-Eckwall et al, 2001;Haas and Défago, 2005). Antibiotic concentrations in nature may not be enough for this purpose (Fajardo et al, 2009), while low concentrations have pleiotropic effects that are not related to competition (Davies et al, 2006;Linares et al, 2006;Yim et al, 2007;Fajardo and Martinez, 2008;Sengupta et al, 2013;Andersson and Hughes, 2014;Goneau et al, 2015;Martínez, 2017;Xiong et al, 2017). However, low individual concentrations of a cocktail of antibiotics could have a combined effect [reviewed by Danner et al (2019)].…”
Section: Introductionmentioning
confidence: 99%